Pernikahan di Bawah Umur dalam Prespektif Hukum Islam dan Hukum Perdata di Indonesia (Studi Kasus Desa Pakue Kecematan Pakue Utara Kabupaten Kolaka Utara Sulawesi Tenggara). - IKA NURUL ANNISA (Jurnal Syariah Hukum Islam, 2019)
The purpose of this thesis is to describe underage marriage from the perspective of Islamic law and civil law in Indonesia. Case study in Pakue Village, Pakue Utara District. As for the background of this writing, the marriage that took place in Pakue village allegedly occurred because of pregnancy outside of marriage and the parents who arranged for their children to marry. There are different views between Islamic law and civil law in Indonesia, especially in Law No.1 of 1974. The formulation of the problem in this research is what is the perspective of Islamic law and civil law in Indonesia on underage marriage in Pakue village? Meanwhile, the research objective was to determine the perspective of Islamic law and civil law in Indonesia on underage marriages in Pakue village. The research method used is qualitative research methods. Sources of research data were obtained directly from the head of the Office of Religious Affairs (KUA). People who carry out child marriages and research the literature from books and documents. By using the Interview, Observation and Documentation Instruments. Research Results Underage marriage that occurred in North Pakue sub-district in the perspective of Islamic law and civil law in effect in Indonesia, underage marriage is legal in Indonesian civil law if it follows the applicable laws. And in North Pakue sub-district there is a marriage that is not legal according to civil law but it is legal in Islamic law and also legal in terms of Islamic law and civil law